Part of Incomplete Medical Record Documents: Literature Review - Indrayadi, Indrayadi; Asih, Hastin Atas (Universitas Muhammadiyah Semarang Press, 2023)
The study aimed to examine the extent of incompleteness in various sections of medical histories within Indonesian hospitals by conducting a literature review based on inclusion and exclusion criteria. The data were analyzed, and the findings were presented. The databases Google Scholar, Garuda, Emerald, and DOAJ were searched using keywords such as 'medical records' and 'hospitals' between 2018 and 2022, yielding 461 papers. Fourteen papers were selected in the final stage. The most frequently incomplete components of medical record documents include essential reports, authentication, data entry, documentation completion, and record-keeping. To prevent incomplete medical records, comprehensive interventions that provide adequate support and training to all staff members involved in completing patient medical records are necessary.